THE APPLICATION OF THE ACCRUAL BASIS PRINCIPLE IN DYNAMIC BALANCE THEORY FOR ENSURING SUSTAINABILITY IN BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In accrual basis accounting, flows are recorded at the time economic value is created, transformed, exchanged, transferred or settled. The period between the time a payment is accrued and the time it is actually made is recorded as a receivable or payable in the financial accounts. The criterion for recognizing receivables and payables that have arisen is the right to receive or pay cash. The financial condition of the organization in the future period is presented in a resulting balance sheet, which is a function of the balance sheet in the current period and the income received and payments made in the future period. The transfer of funds to the future period for the repayment of incurred liabilities leads to a decrease in cash and a reduction in liabilities. The receipt of cash resources in connection with the receivables incurred leads to a decrease in receivables and an increase in cash. This development is described by the theory of the dynamic balance sheet. The dynamic balance sheet is an auxiliary tool for forecasting the financial result and is not part of the annual financial statement of the organization. The theory of the dynamic balance sheet was introduced by Eugen Schmallenbach, a representative of the German accounting school. E. Koisol, his follower, further developed this theory through the concept of the Patagoric balance sheet he developed. The dynamism of the information in the balance sheet reflects the effects of applying the accrual basis in statics and dynamics. The methods of analysis and synthesis, observation and comparison, analogy, modeling and accounting methods of balance sheet summarization were used. The preparation of a dynamic balance sheet allows for the expansion of the application of the accrual basis in budgeting in the private and public sectors.